18F-FDG MicroPET and MRI Targeting Breast Cancer Mouse Model with Designed Synthesis Nanoparticles. (2nd June 2022) - Rezaei Aghdam, Hakimeh; Bitarafan Rajabi, Ahmad; Sadat Ebrahimi, Seyed Esmaeil; Beiki, Davood; Abdi, Khosrou; Mousavi Motlagh, Seyed Shahaboddin; Kiani Dehkordi, Banafsheh; Darbandi Azar, Amir; Shafiee Ardestani, Mehdi
Abstract : The first aim of this study was the development of real-time, quantitative, and noninvasive visual observation that necessitates different noninvasive multimodal imaging methods. Second, the design of a high-sensitivity imaging free-ligand green chemistry nanoprobe is a critical diagnosis of breast cancer mouse models. The gadolinium-based nanoparticles as box-Behnken design (BBD) experiment are synthesized. A small biomolecule L-glutamine is attached to its surface nanoparticles as a template. Large surface-area-to-volume ratios of nanoparticles enhance the capacity for interactions with biomolecules and present more sites for conjugation. G. 2-Deoxy-2[ 18 F]fluoro-D-glucose ([ 18 F]F-FDG) is a quantitative and sensitive tracking instrument in Positron Emission Tomography (PET), also applicable for the in vivo and in vitro characterization of L-glutamine SiGdNPs. Optical imaging was done for 4T1 breast cancer tumor-induced mice. 18 F-NP uptake values were significantly higher in primary breast cancer and brain tumors than [ 18 F]F-FDG in PET at 30 min, injected (20 μ l/g) via the tail vein with about 300 μ Ci of 18 F-FDG loading. After 15 min of the administration of injection (26 μ l/g), the first passed the lung intravenously without any injury to the lung showing promising T1-T2 MRI contrast properties. We receive these by application of a variety of imaging modalities, especially microPET and MRI.